A true four quadrant matrix converter induction motor drive with servo performance - Sunter, S; Clare, JC (I E E E, 1996)
[Abstract Not Available]
27th Annual IEEE Power Electronics Specialists Conference (PESC 96) -- JUN 23-27, 1996 -- BAVENO, ITALY